A smart and sensitive sensing platform to monitor the extracellular concentration of hydrogen peroxide in rat brain microdialysates during pathological processes based on mesoporous silica nanoparticles. Issue 36 (4th September 2018) - Xu, Guoyan; Xie, Qunfang; Chen, Zhonghui; Luo, Fang; Qiu, Bin; Guo, Longhua; Lin, Zhenyu
Abstract : An effective and biocompatible H2 O2 stimuli-responsive chemical sensing platform has been developed based on mesoporous silica nanoparticles (MSNPs). Abstract : Extracellular hydrogen peroxide (H2 O2 ) plays a significant role in regulating a variety of neural functions, such as atherosclerosis, ischemia and so on. It is necessary to develop a sensing platform for monitoring H2 O2 in the central nervous system, especially during pathological processes. However, the design and synthesis of fluorescent probes, which can detect H2 O2 in living cells or tissue, still have problems with toxicity. Herein, an effective and biocompatible H2 O2 stimuli-responsive chemical sensing platform has been developed based on mesoporous silica nanoparticles (MSNPs). Firstly, MSNPs were functionalized with phenylboronic acid groups. Then the functionalized MSNPs reacted with glucose modified Au nanoparticles (Au NPs@glucose) through the carbohydrate–boronic acid interaction, encapsulating the molecular cargo inside the MSNPs. Transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET), and zeta potential were employed to characterize the morphology and surface properties of these materials. The cargo was held in the blocked mesopores of the MSNPs with high efficiency and almost no leakage was detected. The target, H2 O2, oxidized the arylboronic esters, causing the release of Au NPs from MSNPs and thereby resulting in the release of cargo. This sensing platform can be used to monitor the extracellular H2 O2 concentration, which will help in physiological and pathological studies associated with H2 O2 in the rat brain.